Portrayals of Qing Battles - Michaela Pejčochová (Asian Studies)
The collection of the National Gallery in Prague includes two depictions of Qing dynasty battles during the Nian rebellion (1851–1868). These paintings have been studied by researchers, but the complex historical background of their acquisition and movement among Western collections was never clarified. Also, the sad process of how the paintings became orphaned from the matching inscriptions, which were still with them in the mid-20th century, has not been described before. After making new discoveries in the archives of institutions and individual collectors in the Czech Republic and Germany, this article discusses in detail the movements of the paintings among collections and their place in the collecting discourse throughout the 20th century. Their biography is a vital testimony to the complex processes of looting, appropriation, confiscation, damage and rediscovery, which affected numerous artworks and their collections in the tumultuous period of the last century.